The atypical homeoprotein Pbx1a participates in the axonal pathfinding of mesencephalic dopaminergic neurons - Sgadò, Paola; Grbec, Daniel; Simon, Horst (Neural development, 2012)
Background: The pre B-cell leukemia transcription factor 1 (Pbx1) genes belong to the three amino acid loop extension family of homeodomain proteins that form hetero-oligomeric complexes with other homeodomain transcription factors, thereby modulating target specificity, DNA binding affinity and transcriptional activity of their molecular associates. Results: Here, we provide evidence that Pbx1 is expressed in mesencephalic dopaminergic neurons from embryonic day 11 into adulthood and determines some of the cellular properties of this neuronal population. In Pbx1-deficient mice, the mesencephalic dopaminergic axons stall during mid-gestation at the border between di- and telencephalon before entering the ganglionic eminence, leading to a loose organization of the axonal bundle and partial misrouting. In Pbx1-deficient dopaminergic neurons, the high affinity netrin-1 receptor, deleted in colon cancer (DCC), is down-regulated. Interestingly, we found several conserved Pbx1 binding sites in the first intron of DCC, suggesting a direct regulation of DCC transcription by Pbx1. Conclusions: The expression of Pbx1 in dopaminergic neurons and its regulation of DCC expression make it an important player in defining the axonal guidance of the midbrain dopaminergic neurons, with possible implications for the normal physiology of the nigro-striatal system as well as processes related to the degeneration of neurons during the course of Parkinson’s disease.
Gesehen am 20.07.2018